Experiências de governança metropolitana internacional: Os casos dos Estados Unidos e do Canadá - Karla França; Bernardo Alves Furtado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper focus on aspects of metropolitan governance of the United States and Canada highlighting strategies of cooperation and criteria used in their experiences of management and institutionalization. Thus, it describes both the governance experiences implemented voluntarily or compulsorily, their financing mechanisms and the resulting ability to offer public services. Besides, aiming at further deepening the understanding of the strategies adopted, this paper depicts the processes of conurbation, urban sprawl and densification in metropolitan areas. Therefore, the objective of this paper is to analyze the institutional processes of metropolitan governance and its fostering of public policies and programs. Institutional guidelines, challenges and observed limitations are considered for the cases at hand. In order to develop the paper, specific literature produced by the institutions as well as their analysis was consulted. The analyses indicate that there are different governance structures in Canada and in the United States concerning both political attachment and concentration or fragmentation of decision-making processes although delimitation criteria of metropolitan areas are similar. There is a diversity of models for offering public services. However, some limitations can still be observed in terms of articulating policies among different sectors. Disagreements persist among public and private economic actors.
Keywords: H7; R58; Z18; 330; metropolitan areas; institutions; the United States; Canada; metropolitan governance